2016
DOI: 10.1016/j.maturitas.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

EMAS recommendations for conditions in the workplace for menopausal women

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk Contributors: Amanda Griffiths and Margaret Rees prepared the initial draft, which was circulated to EMAS board members for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 19 publications
1
24
0
1
Order By: Relevance
“…An upward trend in life expectancy has led women to spend a third of their lives in post- menopause [ 11 ], in addition the improvement in standards of living has been affecting the rate of perimenopausal and postmenopausal women [ 12 ]. This leads to an increased involvement of middle-age women in the workforce [ 13 ]. Various studies have revealed that menopausal symptoms predominantly affect women in the workforce than those out of the workforce [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…An upward trend in life expectancy has led women to spend a third of their lives in post- menopause [ 11 ], in addition the improvement in standards of living has been affecting the rate of perimenopausal and postmenopausal women [ 12 ]. This leads to an increased involvement of middle-age women in the workforce [ 13 ]. Various studies have revealed that menopausal symptoms predominantly affect women in the workforce than those out of the workforce [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…With rising employment rates for women and an ageing profile of the workforce in the UK and most European countries, increasing numbers of women will be working during their menopause transition and postmenopause. 1,2 As a result there is growing interest in improving the health and wellbeing of working women, and retaining and increasing the numbers of experienced older women in the workplace. Recent recommendations and guidance also stress the importance of improving the experience of menopause for working women.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been given to the management and treatment of menopausal symptoms in the workplace in many countries (Griffiths et al, 2016;Jack et al, 2016). Part-time workers may access drugstores where they can consult with pharmacists rather than visiting hospitals because of not having sufficient time.…”
Section: Discussionmentioning
confidence: 99%